PREDIKSI JUMLAH PENONTON VIDEO YOUTUBE MENGGUNAKAN MODEL DEEP NEURAL NETWORK (DNN) - Indrawan, Dwin; Cakrawijaya, Sena Ramadona; Wicaksono, Bagus Dwi; Erni, Erni; Gata, Windu (Journal of Information System, Informatics and Computing; Vol 5 No 1 (2021): JISICOM : Volume 5, Nomor 1, Juni 2021, 2021)
Youtube viewer becomes a major factor in a content creator's success. The problem is how can predict the number of viewers of a youtube content to determine the success of a content or make it a trending video topic. A machine or computer can predict the number of viewers using the ANN method. DNN is one of ANN models that can predict a dataset. This study compared the success rate in predicting the number of viewers of youtube content from Youtube API dataset. DNN model prediction results have a higher level of excellence compared to the use of traditional methods Linear Regression and Naive Bayes.